A capability framework to develop leadership for evidence-informed therapies in publicly-funded mental health services. Issue 3 (23rd October 2017) - Lau, Geoffrey; Meredith, Pamela; Bennett, Sally; Crompton, David; Dark, Frances
Abstract : Purpose: It is difficult to replicate evidence-informed models of psychosocial and assertive care interventions in non-research settings, and means to determine workforce capability for psychosocial therapies have not been readily available. The purpose of this paper is to describe and provide a rationale for the Therapy Capability Framework (TCF) which aims to enhance access to, and quality of, evidence-informed practice for consumers of mental health services (MHSs) by strengthening workforce capabilities and leadership for psychosocial therapies. Design/methodology/approach: Guided by literature regarding the inadequacies and inconsistencies of evidence-informed practice provided by publicly-funded MHSs, this descriptive paper details the TCF and its application to enhance leadership and provision of evidence-informed psychosocial therapies within multi-disciplinary teams. Findings: The TCF affords both individual and strategic workforce development opportunities. Applying the TCF as a service-wide workforce strategy may assist publicly-funded mental health leaders, and other speciality health services, establish a culture that values leadership, efficiency, and evidence-informed practice. Originality/value: This paper introduces the TCF as an innovation to assist publicly-funded mental health leaders to transform standard case management roles to provide more evidence-informed psychosocial therapies. This may have clinical and cost-effective outcomes for public MHSs, the consumers, carers, and family members.